FEM analysis of micro/meso-scale tooling of a precision machining unit - Cheng, Marcus Jian Yong (2015)
Machining is adversely affected by chatter. To identify chatter-free operating zones, the frequency response functions (FRFs) of the machine structure are required. However, physically acquiring them for large numbers of tool-toolholder-machine combinations is tedious. It is also impractical for delicate micro milling tools. Using receptance coupling methods, a single machine structure response can be combined with a database of individual tool data to form the complete tool point response. The project derived and verified the coupling algorithm using experimental and finite element methods. Modal testing was carried out on the machine tool structure while the predicted attached tool was modelled with finite elements. Receptance coupling was used to combine the FRFs to obtain the predicted dynamic response of the entire assembly. To further ease the practical usage, the algorithm also tested analytical beam approximations in place of the finite element model. This allowed the tool data to be described by simple parameters instead of complex fluted geometry. The results were evaluated to gauge the feasibility of the various methods.